Strategi Pembinaan dan Pengembangan Kepala Sekolah - Fathoni, Tamrin (Civiliza Publishing, Indonesia., 2024)
The aim of writing this work is to find out strategies for coaching and developing school principals in line with the development of education in the current era. This research uses a comprehensive literature review method by searching for information from various sources such as scientific journals, textbooks and research reports. Data was obtained from literature related to leadership and education as well as documents such as school principal development guidelines. Data analysis was carried out descriptively by identifying main themes, summarizing information, and interpreting findings to draw conclusions. The results of this work, namely the coaching and development of school principals, are important for improving the quality of education, through careful selection and increasing competence in accordance with individual needs. These programs aim to address leadership and managerial challenges in a dynamic educational environment. Investment in the development of school principals is a strategic step to ensure the progress and effectiveness of education in the future. The selection of school principals must be based on comprehensive criteria, both academic and non-academic. School principals have an important role in leading and managing educational institutions, with the hope of having competence in various aspects such as leadership, managerial, supervisory, social and entrepreneurial to improve the learning process.